Experiences and observations from a care point for displaced Ukrainians: a community case study in Antwerp, Belgium - Morreel, Stefan; Verhoeven, Veronique; Bastiaens, Hilde; Monten, Katrien; van Olmen, Josefien (Frontiers in Public Health, 2024)
Background A total of 7,307 Ukrainian refugees moved to Antwerp, Belgium, during the study period (01 April 2022 to 31 December 2022). The city’s administration set up three care centers where these people were introduced to the Belgian primary care system, a medical file was created, and acute/preventive/chronic care was delivered. This community case study analyzes the organization and contents of care and reflects upon its meaning for the mainstream healthcare system. Methods This is an observational study using routine electronic medical record data to measure the uptake of care. For a sample of 200 subjects, a retrospective chart review was conducted. Participants All refugees with a medical file at one of the three participating care centers were included. Main outcomes For the observational study, 2,261 patients were reached (30% of the potential users), and 6,450 contacts were studied. The nurses (including midwives) conducted 4,929 out of 6,450 (76%) of all consultations, while the general practitioners (GPs) conducted 1,521 out of 6,450 (24%). Of the nurse consultations, 955 (19%) were followed by another nurse consultation and 866 (18%) by a GP consultation. In the structured case reviews, most contacts were concerned with acute problems (609 out of 1,074, 57%). The most prevalent reasons for encounters and diagnoses were typical primary care issues. The nurses were able to manage half of the cases independently (327, 55%), referred 37% (217) of cases to the GP, and consulted a GP (live, by telephone, or a dedicated app) for 8% (48) of cases. GPs mostly prescribed drugs, referred to a medical specialist, and advised over-the-counter drugs, while nurses more often advised over-the-counter drugs (mostly paracetamol, nose sprays, and anti-inflammatory drugs), provided non-medical advice, or ordered laboratory tests. Discussion The medical care points delivered mostly typical acute primary care in this first phase, with a key role for nurses. The care points did not sufficiently take up chronic diseases and mental health problems. These results will inform policymakers on the use of primary care centers for newly arriving patients in times of a large influx. A nurse-first model seems feasible and efficient, but evaluation of safety and quality of care is needed. Once the acute phase of this crisis fades away, questions about the comprehensiveness, continuity, and integration of care for migrants remain relevant.